Schering en inslag, samenwerken aan meer verwevenheid! Een verkennend onderzoek naar de haalbaarheid van een agglomeratie Twente-Münsterland - Bogaarts, René (Eine besondere Nachbarschaft. Zusammenfassungen ausgewählter Abschlussarbeiten des Masterstudiengangs Niederlande-Deutschland-Studien = Een bijzonder nabuurschap. Samenvattingen van geselecteerde eindscripties van de masterstudie Nederland-Duitsland-Studies, 2023)
Keywords: Arbeitsmarkt; Grenzarbeitnehmer; Grenzüberschreitende Kooperation; Münsterland; Münsterland (West); Twente

Die Grenzstadt als Touristenmagnet - Bongers, Marie (Eine besondere Nachbarschaft. Zusammenfassungen ausgewählter Abschlussarbeiten des Masterstudiengangs Niederlande-Deutschland-Studien = Een bijzonder nabuurschap. Samenvattingen van geselecteerde eindscripties van de masterstudie Nederland-Duitsland-Studies, 2023)
Keywords: Kleve (Kreis Kleve); Tourismus

Das Kampfgebiet zwischen Maas und Rhein in der Periode September 1944 bis März 1945 - Heemels, Jan (Eine besondere Nachbarschaft. Zusammenfassungen ausgewählter Abschlussarbeiten des Masterstudiengangs Niederlande-Deutschland-Studien = Een bijzonder nabuurschap. Samenvattingen van geselecteerde eindscripties van de masterstudie Nederland-Duitsland-Studies, 2023)
Keywords: Befreiung; Rhein-Maas-Gebiet; Soldat; Zweiter Weltkrieg

In welche Klinik? Entscheidungskriterien niederländischer Notfallsanitäter*innen bei der Wahl der Zielklinik im Falle eines ST-Strecken-Hebungsinfarkts im grenzüberschreitenden Kontext - Pilkahn, Kai Annabel (Eine besondere Nachbarschaft. Zusammenfassungen ausgewählter Abschlussarbeiten des Masterstudiengangs Niederlande-Deutschland-Studien = Een bijzonder nabuurschap. Samenvattingen van geselecteerde eindscripties van de masterstudie Nederland-Duitsland-Studies, 2023)
Keywords: Achterhoek (Landschaft); Bocholt; Grenzüberschreitende Kooperation; Krankenhaus; Medizinische Versorgung; Münsterland (West); Winterswijk

Het Duitslandbeeld en het Nederlandbeeld van scholieren in de grensregio - Pollemans, Robine (Eine besondere Nachbarschaft. Zusammenfassungen ausgewählter Abschlussarbeiten des Masterstudiengangs Niederlande-Deutschland-Studien = Een bijzonder nabuurschap. Samenvattingen van geselecteerde eindscripties van de masterstudie Nederland-Duitsland-Studies, 2023)
Keywords: Deutschlandbild; Euregio Rhein-Waal; Niederlandebild; Schüler; Schüleraustausch

Native Borderland Children in the Belgian-German and Polish-German Borderlands. Comparing Verification and Nationalisation Narratives After the Second World War - Venken, Machteld (No Neighbors' Lands in Postwar Europe. Vanishing Others, 2023)
Keywords: Belgien; Deutschland; Kind; Nationalbewusstsein; Polen

Peripheries at the centre. Borderland schooling in interwar Europe - Venken, Machteld (Berghahn Books, 2021)
Aus dem Verlagstext: „Following the Treaty of Versailles, European nation-states were faced with the challenge of instilling national loyalty in their new borderlands, in which fellow citizens often differed dramatically from one another along religious, linguistic, cultural, or ethnic lines. Peripheries at the Centre compares the experiences of schooling in Upper Silesia in Poland and Eupen, Sankt Vith, and Malmedy in Belgium — border regions detached from the German Empire after the First World War. It demonstrates how newly configured countries envisioned borderland schools and language learning as tools for realizing the imagined peaceful Europe that underscored the political geography of the interwar period.“
Keywords: Belgien; Bildungswesen; Deutschland; Eupen-Malmedy; Polen; Schule; Schulpolitik; Sprachpolitik

The Bottom-Up Approach. Experiences with the Impact Assessment of EU and National Legislation in the German, Dutch and Belgian Cross-Border Regions - Unfried, Martin; Kortese, Lavinia Susan Josephine; Bollen-Vandenboorn, Anouk (Territorial Impact Assessment, 2020)
Aus den Verlagsangaben: „Considering the myriad cross-border regions that the EU counts, it is impossible for the European Commission to map detailed territorial cross-border effects in all of the EU’s border regions for the impact assessments it conducts. National governments also face obstacles when seeking to cohesively integrate cross-border impact assessments in the existing frameworks that they use to assess the impact of new legislative, policy and enforcement measures. Even border regions or cross-border entities themselves face challenges in implementing impact assessments in their own territories. Despite the need for structural analyses of the border effects of newly adopted legislation and legislation under review, in terms of policy and enforcement, there are issues regarding the availability of academic resources, relevant tools and know-how. For the last couple of years, researchers from Maastricht University have been assessing as a bottom up exercise the potential effects of legislative proposals on the specific Dutch/German and Dutch/Belgium cross-border territories. This article presents the methodology used and the experiences gained from 2016 to 2019 by highlighting a number of interesting cases. It also offers future ideas for conducting similar “bottom-up” regulatory territorial impact assessments in cross-border regions.“
Keywords: Euregio Maas-Rhein; Gesetzgebung; Grenzgebiet; Wirtschaftsbeziehungen; Wirtschaftsentwicklung

Living in the house of the hangman. Post-war relations between Jews and non-Jews in the German-Dutch border region - Demant, Froukje (Juden und Nichtjuden nach der Shoah. Begegnungen in Deutschland, 2019)
Keywords: Emsland; Grafschaft Bentheim; Juden; Judenverfolgung; Judenvernichtung; Ländlicher Raum; Münsterland (West); Rückkehr; Überlebender

Europäische Integration und Europa der Regionen. Überlegungen zur Geschichte der grenzüberschreitenden Zusammenarbeit in den Beziehungen Belgiens und Nordrhein-Westfalens - Brüll, Christoph (Geschichte im Westen, 2015)
Keywords: Europäische Integration; Grenzüberschreitende Kooperation; Nordrhein-Westfalen

„Die geographische Lage hat uns zu Nachbarn gemacht. Eine stetige Zusammenarbeit hat uns zu Partnern gemacht.“ Die deutsch-belgischen Wirtschaftsbeziehungen seit 1945 und die Schlüsselrolle einer Grenzregion - Quadflieg, Peter M. (Geschichte im Westen, 2015)
Keywords: Ostbelgien; Wirtschaftsbeziehungen; deutsch-belgische Beziehungen

"Left to Their Own Devices". Belgium's Ambigious Assimilation of Eupen-Malmedy (1919–1940) - O'Connell, Vincent (Revue Belge d’Histoire Contemporaine, 2013)
„The inter-war period in Eupen-Malmedy remains a sensitive arena in which the experiences and sensibilities of its inhabitants have barely been broached by historians. The controversial milestones of the interwar period in Eupen-Malmedy have been covered over with the palimpsest of what the late Tony Judt has referred to elsewhere as ‘selective forgetting’ where communities as well as individuals shield certain episodes or events of the past from intrusion by historians1. The German historian Freddy Cremer describes this phenomenon as akin to ‘amnesia as therapy’. The period following the Nazi invasion and annexation of the former Germany districts in 1940 and their later liberation conspired to further compound an already complex situation. Since then the historical narrative has been shrouded beneath a veil of silence. This article aims in some small way to pull back this veil so that in Cremer’s words “the past may not be left untouched”.“
Keywords: Annexion; Eupen-Malmedy; Staatsgrenze; Versailler Vertrag (1919)

Die kartographiehistorischen Forschungen von Gerhard Aymans im Rhein-Maas-Gebiet - Krings, Wilfried (Entdeckungslandschaft Unterer Niederrhein - Land zwischen Maas und Rhein. Neue Forschungen zur Kulturlandschaft des Niederrheins auf der Grundlage der Arbeiten von Gerhard Aymans und Rudolf Straßer. Symposium im Kloster Graefenthal, Goch-Asperden, 2006, 2008)
Keywords: Historische Karte; Historische Kartografie; Kartografie; Niederrhein-Gebiet; Rhein-Maas-Gebiet

Die Bedeutung der Forschung von Prof. Dr. Gerhard Aymans für das niederländische Nordlimburg - Renes, Hans; Storms, Martijn (Entdeckungslandschaft Unterer Niederrhein - Land zwischen Maas und Rhein. Neue Forschungen zur Kulturlandschaft des Niederrheins auf der Grundlage der Arbeiten von Gerhard Aymans und Rudolf Straßer. Symposium im Kloster Graefenthal, Goch-Asperden, 2006, 2008)
Keywords: Historische Karte; Historische Kartografie; Kartografie; Kataster; Kleve (Kreis Kleve)

Preußischer Westen - belgischer Osten. Eupen, Malmedy und St. Vith zwischen Reichsgründung und Zweitem Weltkrieg - Koll, Johannes (Comparativ, 2005)
Keywords: Ostbelgien

The border paradox. Uneven development, cross-border mobility and the comparative history of the Euregio Meuse-Rhine - Knotter, Ad (Fédéralisme Régionalisme, 2002)
Keywords: Euregio Maas-Rhein; Grenzverkehr

Das Grenzland von Nordrhein-Westfalen, die Traktatländereien und die niederländischen Grenzkorrekturen 1949 bis 1963 - Woelk, Wolfgang (Zentrum für Niederlande-Studien, Jahrbuch, 1994)
Keywords: Annexion; Auftragsverwaltung; Grenzkonflikt; Nordrhein-Westfalen

Städtedreieck Enschede/Hengelo – Münster – Osnabrück. Rahmenbedingungen, Entwicklungschancen, Gestaltungsmöglichkeiten – Kurzbericht über ein Forschungsprojekt - Michels, Winfried (Zentrum für Niederlande-Studien, Jahrbuch, 1992)
Keywords: Enschede; Grenzüberschreitende Kooperation; Grenzüberschreitende Regionalplanung; Hengelo; Infrastruktur; Münster (Westf); Osnabrück; Raumordnung; Verkehrsplanung; Wirtschaftsbeziehungen

Westmünsterland - Ostniederlande. Entwicklung und Stellung eines Grenzraumes. Vorträge auf der Jahrestagung der Geographischen Kommission in Vreden 1983 - Geographische Kommission für Westfalen (Geographische Kommission für Westfalen, 1984)
Inhaltsverzeichnis: http://digitale-objekte.hbz-nrw.de/storage/2011/09/22/file_4/4295872.pdf
Keywords: Grenzgebiet; Münsterland (West); Niederlande (Ost)

Querelles d’Allemands entre Locarnistes. La Question d’Eupen-Malmédy - Poulain, Marc (Revue historique, 1977)
Keywords: Annexion; Eupen-Malmedy; Versailler Vertrag (1919)

„Grenzland seit Menschengedenken“. Eupen, Malmedy, St. Vith zwischen Wiener Kongress und Versailler Vertrag - Scharte, Sebastian (Internetportal Rheinische Geschichte)
Keywords: Eisenbahn; Katholizismus; Kollektives Gedächtnis; Nationalbewusstsein; Ostbelgien; Öffentlichkeit